2011
DOI: 10.1590/s1677-55382011000200011
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal and molecular abnormalities in a group of Brazilian infertile men with severe oligozoospermia or non-obstructive azoospermia attending an infertility service

Abstract: Purpose: To determine the frequency of genetic alterations in a population of Brazilian infertile men with severe oligozoospermia or non-obstructive azoospermia. Materials and Methods: Retrospective study of a group of 143 infertile men with severe oligozoospermia or non-obstructive azoospermia from the Andrology Outpatient Clinic of the Human Reproduction Service at the ABC School of Medicine. Of these patients, 100 had severe oligozoospermia, and 43 non-obstructive azoospermia. All patients underwent a genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 32 publications
4
35
0
1
Order By: Relevance
“…Mafra et al (2011) reported chromosomal abnormalities for 6.2% of infertile Brazilian men with severe oligozoospermia or non-obstructive azoospermia and the total prevalence of chromosomal abnormalities was found to be 11.2% in infertile males with oligozoospermia and azoospermia in southeast Turkey (Balkan et al, 2008). Ocak et al (2014) reported structural or numerical chromosomal abnormalities to be present in 12% of patients with azoospermia or severe oligospermia and 10.9% of Chinese patients with azoospermia or severe oligozoospermia were found to have chromosomal abnormalities (Zhou-Cun et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Mafra et al (2011) reported chromosomal abnormalities for 6.2% of infertile Brazilian men with severe oligozoospermia or non-obstructive azoospermia and the total prevalence of chromosomal abnormalities was found to be 11.2% in infertile males with oligozoospermia and azoospermia in southeast Turkey (Balkan et al, 2008). Ocak et al (2014) reported structural or numerical chromosomal abnormalities to be present in 12% of patients with azoospermia or severe oligospermia and 10.9% of Chinese patients with azoospermia or severe oligozoospermia were found to have chromosomal abnormalities (Zhou-Cun et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Of the 32 selected studies 14 are from descriptive [1, 2, 4, 13, 24, 27-29, 31, 32, 34-37], 08 are cross-sectional [3,5,17,18,21,25,26,33], 05 are experimental [7,12,19,20,38], 03 are case reports [22,30,39] and 02 are case-control studies [10,23]. Studies have good methodological accuracy.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have good methodological accuracy. The sample universe is quite heterogeneous, given the very design of the studies (22 case reports with 02 individuals up to 33 cross-sectional studies with 4, 441 individuals), age differences between individuals in the samples ranging from 17 years [10] to 66 years [21], as well as the origin of the patients who were: India [2,23,25,35], Brazil [3,31,34,36], China [4,10,17,18], Iran [1,7,19,21] Turkey [5,26,27] [20], Denmark [37], USA [22], england [38], Mexico [30], Serbia [28] and Venezuela [32]. Because of this situation, the data becomes divergent and the comparative analysis becomes troublesome.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations